The Economic Geography of Internet Infrastructure in the United States - Shane M Greenstein (Northwestern University, Center for the Study of Industrial Organization (CSIO), 2004)
In this review article I place industrial economics at the center of the explanation for the geographic properties of Internet infrastructure, applying this established mode of analysis to the unique cost structures and demand characteristics of these markets. I begin with an overview of the origins of the Internet and why the economic geography of Internet infrastructure was unclear prior to commercialization. The next sections analyze four overlapping markets of Internet infrastructure: dial-up service, backbone, broadband, and business provision of Internet infrastructure services. The concluding section summarizes the answers to several key questions motivating this broad research area.
Keywords: 330; Internet; Netzinfrastruktur; Service Provider; Breitbandkommunikation; Wirtschaftsgeographie; USA